Pelatihan Google Families untuk Membangun Kebiasaan Teknologi Sehat di Kelurahan Jati Kota Probolinggo - Putri Susanti, Anindya; Nurul Shodiqoh, Hanifah; Imamatul Chusniyah, Danis; Prasetya, Benny (Profetik: Jurnal Pengabdian Masyarakat, 2024)
Smartphones represent a prominent form of information and communication technology, widely adopted due to their convenience, sophistication, and connectivity to the internet. Children, as users of smartphones, face potential negative consequences stemming from their use of these devices. It is essential for parents, who are the closest individuals to their children, to possess adequate knowledge regarding the management and supervision of smartphone usage to mitigate adverse effects. Google Family Link is an application that can help parents monitor and control their children's smartphone usage. Training and guidance on this application can be provided to support parents in supervision and control. Through this training, it is hoped that parents can understand and use the Google Family Link application well. These guidance and training activities are expected to provide significant benefits for mothers.